The Effect of Three Block-Pedal Angles on Kinematics of the First Contact during a Sprint-Start Performance - Hussain, Murtaza; Nishan Singh Deol; Dhananjoy Shaw (Program Pascasarjana Universitas Negeri Jakarta, 2023)
Athletes have considerable freedom in altering the block spacing and block obliquity to personalize it to their convenience, they have relied on experience to develop the bock configuration of their preference. There is little research exploring this area and is therefore worthy of scrutiny. So the objective was to test if the alterations in the block-pedal angles continue their effect until the First step in a sprint start performance.2-D videography method was used to study the sprint start performance of five highly trained athletes. One-way ANOVA was used to determine the deference in lower-limb kinematics at the first contact at various block angles. The results showed no statistical difference between the kinematics of the lower limbs at the initial contact at various block-obliquities. The study concluded that there was no measurable difference in the kinematics at initial contact of highly trained athletes.